2021
DOI: 10.1002/sres.2790
|View full text |Cite
|
Sign up to set email alerts
|

Automated content analysis: The review of the big data systemic discourse in tourism and hospitality

Abstract: Tourism is one of the economic activities that has changed most since large‐scale multidimensional data set, so‐called big data, was provided. The scientific literature on big data and tourism with the hospitality industry has been growing exponentially, which is, for this reason, hard to comprehend and synthesise manually. Our research question is how to familiarise oneself with the current knowledge of the relationship between the big data and the complex changes in the tourism and hospitality industry. An a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…Social entrepreneurship can help develop sustainable, innovative (technological) approaches that help reduce human emissions and thus increase community development [96]. It is identified that state-of-art information and communication technologies play a crucial role when it comes to the revival of the (sustainable) tourism sector in the post-COVID-19 era, especially data mining [97,98], virtual reality [99], augmented reality [100] and Internet of Things (IoT) [101]. Data mining aims to discover useful patterns and knowledge from enormous data about events of importance, users, and their interactions with others and the environment.…”
Section: The Role Of Social Innovations and Digitalization In Tourism...mentioning
confidence: 99%
See 1 more Smart Citation
“…Social entrepreneurship can help develop sustainable, innovative (technological) approaches that help reduce human emissions and thus increase community development [96]. It is identified that state-of-art information and communication technologies play a crucial role when it comes to the revival of the (sustainable) tourism sector in the post-COVID-19 era, especially data mining [97,98], virtual reality [99], augmented reality [100] and Internet of Things (IoT) [101]. Data mining aims to discover useful patterns and knowledge from enormous data about events of importance, users, and their interactions with others and the environment.…”
Section: The Role Of Social Innovations and Digitalization In Tourism...mentioning
confidence: 99%
“…Data mining aims to discover useful patterns and knowledge from enormous data about events of importance, users, and their interactions with others and the environment. Typical scenarios include tourist segmentation based on clustering, tourist number prediction relying on regression, excursion and services cross-selling based on association rule mining and booking cancellation prediction leveraging classification methods [97,98].…”
Section: The Role Of Social Innovations and Digitalization In Tourism...mentioning
confidence: 99%
“…Social entrepreneurship can help develop sustainable, innovative (technological) approaches that help reduce human emissions and thus increase community development [92]. It is identified that state-of-art information and communication technologies play a crucial role when it comes to the revival of the (sustainable) tourism sector in the post-COVID era, especially data mining [93,94], virtual reality [95], augmented reality [96] and Internet of Things (IoT) [97]. Data mining aims to discover useful patterns and knowledge from enormous data about events of importance, users, and their interactions with others and the environment.…”
Section: Category: 2016-2020mentioning
confidence: 99%
“…Data mining aims to discover useful patterns and knowledge from enormous data about events of importance, users, and their interactions with others and the environment. Typical scenarios include tourist segmentation based on clustering, tourist number prediction relying on regression, excursion and services cross-selling based on association rule mining and booking cancellation prediction leveraging classification methods [93,94].…”
Section: Category: 2016-2020mentioning
confidence: 99%
“…The Gephi (Madan et al, 2016;Hernández García et al, 2016) is a freeware, social network analysis, and graph generating tool that works based on the principles of network and graph theory (Barnes & Harary, 1983). All these tools are widely used in a broad range of thematics (Pucihar, 2020;Peterlin et al, 2020;Roblek et al, 2020) Specifically, from the Leximancer dashboard, we used the features "Concept Maps"…”
Section: Research Walkthroughmentioning
confidence: 99%